2021
DOI: 10.1021/acs.macromol.1c00100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Labile Mesogens on the Morphology of Liquid Crystalline Block Copolymers in Thin Films

Abstract: The self-assembly of liquid crystals (LCs) in small volumes is mediated by the anchoring conditions of the constituent mesogens at the confining surfaces. In hierarchically ordered systems such as LC block copolymers, the importance of anchoring at external as well as internal interfaces can give rise to intriguing phenomena. Here, we examine the morphology of thin films of liquid crystalline block copolymers (LC BCPs) in the presence of non-bonded, or labile, mesogens and explore the manner in which external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Recent work by Osuji et al presented a different approach to manipulate thin-film morphologies in LC BCPs. 39 The method relies on blending labile mesogens with neat LC BCPs (Figure 3i). The CB-and poly(lactic acid) (PLA)-based side chain LC BCPs used for the study formed parallel lamellae and cylinders as neat materials (i.e., without additives) in thin films.…”
Section: ■ Self-assembly Of Lc Block Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Osuji et al presented a different approach to manipulate thin-film morphologies in LC BCPs. 39 The method relies on blending labile mesogens with neat LC BCPs (Figure 3i). The CB-and poly(lactic acid) (PLA)-based side chain LC BCPs used for the study formed parallel lamellae and cylinders as neat materials (i.e., without additives) in thin films.…”
Section: ■ Self-assembly Of Lc Block Copolymersmentioning
confidence: 99%
“…On the left side, AFM images show parallel cylinders and lamellae (top and bottom, respectively), and on the right side, AFM images show perpendicular cylinders and lamellae (top and bottom, respectively). Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Nanopatterning With Lc Block Copolymers and Oligomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐assembly through phase separation in the BCs generally occurs by two major processes called thermal annealing 67–69 and solvent vapor annealing (SVA) 70–72 to enhance the mobility of block copolymer chains, and thus produce a morphology at thermodynamic equilibrium. Among these annealing techniques, the SVA is known to be a simple, rapid, low‐cost, versatile and highly efficient technique for producing highly ordered microdomains at room‐temperature 71,73 .…”
Section: Introductionmentioning
confidence: 99%
“…However, most oriented nanostructures studied so far have been of cylindrical morphologies, and the oriented LAM morphology with a higher f value has rarely been reported. 24 Stein and co-workers studied the LAM structure of the diblock copolymer of polystyrene (PS) and a PIL poly(1-(2-acryloyloxyethyl)-3-butylimidazolium bis(trifluoromethanesulfonyl)imide). 25 They demonstrated that the ion conductivity of PS-PIL BCPE films was approximately 20 times higher in the perpendicular direction than in the through-plane direction.…”
Section: Introductionmentioning
confidence: 99%